The efficacy evaluation of mutant strain ΔpilV-AH as a live attenuated vaccine in Leiocassis longirostris - Jiayan Ran; Xueyang Zhang; Yifan Zhang; Wenfeng Liu; Feng Xu; Zhongwei Wang; Jie Mei; Guangjun Lv; Hui Luo; Ronghua Wu; Hua Ye (Fish & Shellfish Immunology, 2026)

MCM-41 induced NiCe synergistic constructs Ni-OV-Ce interface for enhanced oxygen transfer in dry methane reforming - Yuanjing Ran; Xing Yi; Daoping Ye; Tao Zhang; Li Lv; Wenxiang Tang; Yan Wang; Zongpeng Zou; Shengwei Tang (Chemical Engineering Journal, 2026)

Volatile methylsiloxanes in a textile dyeing and printing industrial park: Source profiles, ambient distributions and SOA formation potential - Xiaodie Pang; Hao Han; Wei Song; Xiangyu Zhang; Ran An; Jianqiang Zeng; Chao Peng; Weiqiang Yang; Chenshuo Ye; Xiao Tian; Hongcheng Lu; Zhou Zhang; et al. (Journal of Hazardous Materials, 2026)

Improving the accuracy of phase distribution measurement with ERT in multiphase flows by correcting fringe-effect artifacts - Ran Pang; Chao Wang; Xiao Liang; Jiamin Ye (Chemical Engineering Journal, 2026)

TRIF signaling is essential for the activation of dendritic cells during porcine rotavirus infection - Yu Sun; Tianming Niu; Ran Zhang; Danni Li; Mingyang Cheng; Chenxi Jiang; Yiran Shao; Hongyuan Wang; Ziqun Guo; Wentao Yang; Xin Cao; Chunfeng Wang; et al. (Veterinary Microbiology, 2026)

Survey of tick species and tick-borne pathogens in pet dogs and cats in mainland China - Qing Ye; Guangbing Zhang; Ran Wang; Jie Cao; Yongzhi Zhou; Yannan Wang; Houshuang Zhang; Jinlin Zhou (Veterinary Parasitology, 2026)

A dual-functional single-crystalline layer boosts operational stability of organic light-emitting diodes - Gao-Da Ye; Guan-Ran Wang; Xue-Peng Wang; Su-Heng Li; Nai-Qi Wang; Hu Zhang; Yu-Ting Huang; Lingjie Sun; Yajing Sun; Fangxu Yang; Jin-Bei Wei; Yue-Feng Liu; et al. (Science Bulletin, 2026)

Permian A-type felsic magmatism in the South Tianshan Orogenic Belt: Crustal melting triggered by the Tarim mantle plume - Zhi-Hao Song; Xian-Tao Ye; Xiao-Qiang Liu; Hong-Ran Wang; Ming-Can Yang; Shun-Hao Fu; Chuan-Lin Zhang (Lithos, 2026)

A self-perpetuating cycle: how heavy metals shape DOM chemistry to promote their own immobilization in soil - Shuyi Zhang; Wenjun Zhang; Ye Li; Longfei Zhao; Chunmei Ran; Hongming Cai; Zhineng Hao; Junjie Zhang; Lei Wang (Environmental Monitoring and Assessment, 2026)

Autophagy is more vital in tomato and citrus than in arabidopsis - Guowang Liao; Haoyang Hu; Peng Zhang; Ran Hu; Saiyu Cao; Ye Guo; Pengwei Wang (Protoplasma, 2026)

Sustainable management of plateau mountainous urban agglomerations based on the ecosystem services supply-demand balance: Application of scale and threshold effects - Xiaobao Wang; Xiaoqing Zhao; Yuju Ran; Yanmin Fan; Wentao Li; Xianmin Ye; Yuqin Zhou; Yanlin Wang; Fei Liu (Journal of Cleaner Production, 2026)

Electromembrane fractionation of lysozyme from salted duck egg white: Process optimization and structural-functional characterization - Shudong He; Min Qiu; Yuanyang Wang; Tong Jin; Yongkang Ye; Walid Elfalleh; Tianjiao Niu; Ran Xiao; Hanju Sun (Food Bioscience, 2026)

Modeling of multisystem coupling evolution and identification of key control factors for liquefied petroleum gas leakage accidents - Xueer Zhang; Sisi Sun; Hongcheng Lu; Ran Ye; Jinghong Wang (Process Safety and Environmental Protection, 2026)

Rainfall-driven shifts in disinfection byproduct precursors in eutrophic lakes: From algal to terrestrial sources - Fangyuan Jiang; Jiaqi Ran; Feifei Wang; Yao Qu; Kaidi Lai; Ruixin Qu; Wenyuan Yang; Cheng Ye; Wenhai Chu (Journal of Hazardous Materials, 2026)

Sustainable recovery of cobalt and lithium from spent lithium-ion batteries using water-based deep eutectic solvents - Pengfei Yang; Linxing Zhou; Jun Zeng; Youming Ye; Junfeng Lan; Xuezhen Xie; Yanmeng Chen; Xiaoshu Wang; Ran Ao (Journal of Environmental Chemical Engineering, 2026)

Microplastic exposure reshapes the virome and virus–bacteria networks with implications for immune regulation in Mytilus coruscus - Jingyan Zhang; Xiaoya Wang; Qingyang Li; Bin Li; Haiping Ma; Shijie Wang; Qianwen Ying; Suzhen Ran; Ekaterina O. Leonteva; Mikhail B. Shilin; Yingying Ye; Xiangli Dong; et al. (Marine Pollution Bulletin, 2026)

Optimization on escape exit selection for personnel in highway tunnel fires - Jinghong Wang; Jintao Li; Hongcheng Lu; Siming Wang; Ran Ye; Jialin Wu (Tunnelling and Underground Space Technology, 2026)

Engineered hydrogels for siRNA delivery: From smart design to therapeutic impact - Shaohui Geng; Yijin Jiang; Huawei Wang; Anqi Liu; Xiuwen Wang; Ran Man; Jingyuan Fu; Yiwei Guan; Zi Ye; Zixuan Shu; Han Sheng; Jinian Wei; et al. (Chemical Engineering Journal, 2026)

Influence of planting patterns on Ligusticum sinense cv. Chuanxiong development and its rhizosphere microenvironment - Lin Liu; Ting Li; Hao-ran Song; Xiu-wen Bao; Jia Ye; Qing-he Wang; Jing Bai; Si-jing Liu; Yang Li; Shu-qi Niu; Jin-lin Guo (Journal of Cleaner Production, 2025)

Quantitative Evaluation of Incomplete Stent Apposition in Intracranial Aneurysms Using Optical Coherence Tomography: a Porcine Model Study - Zhuangzhuang Wei; Ji Ma; Zhike Zhang; Shuailong Shi; Shuhai Long; Shaofeng Shui; Lei Yan; Yan Song; Yi Tang; Ye Wang; Jie Yang; Yuncai Ran; et al. (Translational Stroke Research, 2025)

Clinical validation of artificial intelligence-assisted karyotyping on peripheral blood in a cytogenetic diagnostic laboratory - Yujie Zhu; Matthew Hoi Kin Chau; Huilin Wang; Ning Song; Ran Wei; Kin Wah Suen; Anna Chi Sum Chan; Wan Ching Hung; Ye Cao; Zirui Dong; Tak Yeung Leung; Sau Wai Cheung; et al. (Human Genetics, 2025)
G-banded chromosome analysis, also known as G-banded karyotyping, remains a fundamental and irreplaceable diagnostic modality in clinical genetic testing. G-banded karyotypes provide whole genome visualization through chromosome banding patterns at the single-cell resolution for the diagnosis of chromosomal disorders. However, this method is labor-intensive and requires specialized expertise to manually analyze and karyotype metaphase spreads. In recent years, artificial intelligence (AI) algorithms have been utilized to automate karyotyping and assist with chromosome analysis. Despite this progress, there is a scarcity of studies evaluating the utility of artificial intelligence-assisted (AI-assisted) karyotyping analysis in cytogenetics diagnostic laboratories. This study highlights promising applications of AI-assisted karyotyping analysis in a cytogenetics diagnostic laboratory through a combination of a literature review, our data, and experience from a retrospective cohort study. This study also discusses important considerations of the use of AI-assisted karyotyping analysis in a cytogenetic diagnostic laboratory and outlines a two-stage framework for its implementation into clinical workflows. This approach aims to utilize the accuracy and efficiency of AI-assisted karyotyping analysis, potentially benefiting personalized patient care and contributing to advancements in the health system.

Application potential of UK′37 and TEX86H palaeothermometers in high-energy strait-type marginal seas: a case study in the Taiwan Strait - Chang Ran; Shuqin Tao; Mengyuan Wang; Zhen Jiang; Xiang Ye; Aijun Wang (Marine Geology, 2025)

Explainable transfer learning for subsurface soil moisture prediction - Sheng Ye; Yifan Chai; Jiyu Li; Jingkai Wang; Xuebin Deng; Qihua Ran (Journal of Hydrology, 2025)

Target and non-target screening of per- and polyfluoroalkyl substances (PFAS) in drinking water: Focus on alternatives and health risks - Guojian Shao; Nan Jiang; Tao Liu; You Xia; Ran Liu; Peng Zhang; Ye Wang (Environmental Research, 2025)

Nano polystyrene accelerated the reproductive toxicity induced by the Tris(1,3-dichloro-2-propyl) phosphate via Nhr-69-PISD-Drp-1-mediated mitochondrial fragmentation in Caenorhabditis elegans - Jia Wang; Yingchi Shi; Ke Meng; Mingjun Sun; Han Chen; Nan Jiang; Beijing Cheng; Mohan Hu; Ping Ye; Ran Liu (Environmental Pollution, 2025)

Satellite remote sensing capturing intense ozone production over marginal seas in East Asia: evident influence on air quality in coastal cities - Jin Ye; Qihou Hu; Qin Gao; Ran Zhao; Wenjing Su; Chengxin Zhang; Xiaohan Wang; Ziwei Li; Cheng Liu (Atmospheric Environment, 2025)

Impact of tris (2-chloropropyl) phosphate and triphenyl phosphate on honeybee (Apis mellifera L.) midgut health: Assessing toxicity and potential mitigation with melatonin - Rongyi Ye; Yihan Wang; Kebo Wang; Ran Yi; Fengjiao Sun; Nan Huang; Tianliang Zhang; Yanhua Wang; Chen Chen (Journal of Hazardous Materials, 2025)

Retraction Note: Reconstructing mantle–crust boundary magmatism through Cimmerian orogenic events: evidence from deep crustal cumulates in northeastern Pamir - Masumeh Sargazi; Chuan-Lin Zhang; Yan Jing; Zahid Hussain; Zhi-Hao Song; Hong-Ran Wang; Xiao-Qiang Liu; Xian-Tao Ye (Contributions to Mineralogy and Petrology, 2025)

Effect of H2 content on the evolution process of CH4/H2 explosion pressure and flame structure - Shanshan Liu; Dongxu Huang; Yong Pan; Yingquan Qi; Lingxiu Yan; Zhenhua Wang; Xin Zhang; Ran Ye; Juncheng Jiang (Process Safety and Environmental Protection, 2025)

Optimizing fertilization enhances sustainable vegetable production: combining on-farm composting and biochar application to improve vegetable yield, soil health, and socio-economic benefits - Bihui Tang; Pingping Ye; Xu Luo; Xinyi Yang; Tao Liang; Anle Chen; Duan Yu; Xiaozhong Wang; Ran Xiao (Journal of Cleaner Production, 2025)

Evaluating the combined toxicity of broflanilide and myclobutanil on honeybees (Apis mellifera L.): Molecular mechanisms and protective effects of curcumin - Rongyi Ye; Ran Yi; Yihan Wang; Nan Huang; Yanhua Wang; Chen Chen (Journal of Hazardous Materials, 2025)

Soot particles generated by n-heptane and n-heptane/OME3 in an inverse diffusion flame: A comparative analysis of physical properties and oxidative reactivity - Ye Liu; Ran Zhang; Chenxi Wang; Haibo Chen; Gang Lyu; Jun Wang; Huayu Tian; He Yang; Yajun Wang; Chenyang Fan; Bin Xu; Xiaowei Wang; et al. (Fuel, 2025)

In situ implantable and reactive oxygen species responsive hydrogel loaded with minocycline for functional rehabilitation of traumatic brain injury - Jie Zhou; Yuanyuan Ran; Chenye Qiao; Jingjing Liang; Yufei Wang; Wei Su; Yonghao Xiao; Lin Ye; Jianing Xi; Zongjian Liu (Chemical Engineering Journal, 2025)

Resolving the Snowball Earth conundrum: the role of marine dissolved organic carbon pool - Bing Shen; Xianguo Lang; Ruimin Wang; Yonggang Liu; Shihong Zhang; Tianzheng Huang; Xuelei Chu; Yixin Cui; Weiming Ding; Yuansheng Du; Ran He; Kangjun Huang; et al. (Science Bulletin, 2025)

Application of mass balance and unmixing model to trace sediment sources in an agricultural catchment - Yanrui Yang; Jianfeng Xu; Jie Chen; Wei Ye; Lishan Ran; Kai Wang; Haiming Lu; Xianqiang Tang; Danyang Wang; Deti Xie; Jiupai Ni; Yongyi Cheng; et al. (CATENA, 2025)

Advances and applications in single-cell and spatial genomics - Jingjing Wang; Fang Ye; Haoxi Chai; Yujia Jiang; Teng Wang; Xia Ran; Qimin Xia; Ziye Xu; Yuting Fu; Guodong Zhang; Hanyu Wu; Guoji Guo; et al. (Science China Life Sciences, 2025)

Integrative proteogenomic and pharmacological landscape of acute myeloid leukaemia - Hanlin Wang; Jun-Yu Xu; Tao Wang; Gaoya Xu; Guanghao Luo; Mingya Zhang; Gusheng Tang; Chang Wang; Libing Wang; Weijia Fu; Xiong Ni; Linhui Zhai; et al. (Science Bulletin, 2025)

Experimental and mechanism research on the deflagration characteristics of H2/C2H5OH mixture under non-atmospheric conditions - Yingquan Qi; Ran Ye; Yong Pan; Jingran Liu; Shanshan Liu; Zhenhua Wang (Process Safety and Environmental Protection, 2025)

GeoMagFilter: Modeling the angular-rigidity joint distribution of galactic cosmic rays on low Earth orbit - Long Chen; Ran Huo; Qiyun Li; Taihao Wang; Weiwei Xu; Wenwen Ye (Advances in Space Research, 2025)

Mechanism of Epigallocatechin-3-gallate in the prevention and treatment of irritable bowel syndrome: A network pharmacology and gene expression omnibus chip data-based study - Fangchen Ye; Laifu Li; Lianli Wang; Yan Ran; Lin Mei; Yating Sun; Xinping Zhang; Fei Dai (PharmaNutrition, 2025)

Corrigendum to “Long-term warming and acidification interaction drives plastic acclimation in the diatom Pseudo-nitzschia multiseries” [Mar. Environ. Res. 204 (2025) 106901] - Yanmin Sun; Fan Yang; Ran Duan; Dong Xu; Yanan Zhang; Chengwei Liang; Zhuonan Wang; Xintong Huang; Bingkun Wang; Yapeng Wang; Haoming Sun; Naihao Ye; et al. (Marine Environmental Research, 2025)

Long-term warming and acidification interaction drives plastic acclimation in the diatom Pseudo-nitzschia multiseries - Yanmin Sun; Fan Yang; Ran Duan; Dong Xu; Yanan Zhang; Chengwei Liang; Zhuonan Wang; Xintong Huang; Bingkun Wang; Yapeng Wang; Haoming Sun; Naihao Ye; et al. (Marine Environmental Research, 2025)

Zircon U-Pb ages, trace elements, and Hf isotopes establish a genetic link between volcanic ash beds and porphyritic intrusions during early Silurian in the South China Block - Tianrui Wang; Bo Ran; Shugen Liu; M. Santosh; Zhiwu Li; Yuyue Han; Yuehao Ye (Lithos, 2025)

Deterioration mechanisms of coal mechanical properties under uniaxial multi-level cyclic loading considering initial damage effects - Qican Ran; Yunpei Liang; Zhili Yang; Quanle Zou; Chunfeng Ye; Chenglin Tian; Zhaopeng Wu; Bichuan Zhang; Weizhi Wang (International Journal of Rock Mechanics and Mining Sciences, 2025)

A stab-/solvent-resistant HAG/silicone armor for durably stretchable electroluminescent device - Jun-Yue Li; Xin-Kai Qian; Qi-Ye Wang; Hong-Chao Sun; Xiu-Juan Li; Zhen-Yu Zhang; Chao-Ran Huang; Rui Guo; Fei Xiu; Ju-Qing Liu (Chemical Engineering Journal, 2025)

RETRACTED ARTICLE: Reconstructing mantle–crust boundary magmatism through Cimmerian orogenic events: evidence from deep crustal cumulates in northeastern Pamir - Masumeh Sargazi; Chuan-Lin Zhang; Yan Jing; Zahid Hussain; Zhi-Hao Song; Hong-Ran Wang; Xiao-Qiang Liu; Xian-Tao Ye (Contributions to Mineralogy and Petrology, 2025)

A framework for territorial spatial ecological restoration zoning integrating “Carbon neutrality” and “Human-geology-ecology”: Theory and application - Yuju Ran; Xiaoqing Zhao; Xianmin Ye; Xiaobao Wang; Junwei Pu; Pei Huang; Yuqin Zhou; Junyi Tao; Beihao Wu; Wenwen Dong; Guoxun Qu (Sustainable Cities and Society, 2024)

Spatiotemporal variations of phytoplankton in the Taiwan Strait using lipid biomarkers and the potential influencing factors - Zitong Liu; Shuqin Tao; Xiang Ye; Aijun Wang; Chang Ran; Shuilan Wu; Zhen Jiang; Junwen Wu (Acta Oceanologica Sinica, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Successive application of controlled-loss urea improves grain yield and economic benefit in maize-wheat cropping systems - Lisha Shangguan; Zejie Ye; Dengke Hou; Wenlu Zhai; Zhongzhou Feng; Ran Zhang; Yingxin Xie; Geng Ma; Chenyang Wang; Dongyun Ma; Tiancai Guo; Xu Zhao (European Journal of Agronomy, 2024)

Patterns and drivers of organic carbon in hydromorphic soils across inland aquatic-terrestrial ecotones at the global scale - Yiguo Ran; Peng Wang; Fei Ye; Junfeng Qu; Yang Ning; Yanshuo Zhang; Zhaofei Wen; Shengjun Wu; Ping Huang (CATENA, 2024)

Paleoenvironmental evolution and organic matter accumulation of the lower Cambrian Maidiping marine black shales in the intracratonic basin, western margin of Sichuan Basin, South China - Guodong Xia; Yuehao Ye; Shugen Liu; Heng Wang; Jinmin Song; Wei Sun; Bo Ran; Kun Jiao; Guoliang Xie; Bin Deng; Zhiwu Li; Yun Zeng (International Geology Review, 2024)

Risk analysis of air pollutants and types of anemia: a UK Biobank prospective cohort study - Laifu Li; Yan Ran; Yan Zhuang; Lianli Wang; Jiamiao Chen; Yating Sun; Shiwei Lu; Fangchen Ye; Lin Mei; Yu Ning; Fei Dai (International Journal of Biometeorology, 2024)

Mechanical protein polycystin-1 directly regulates osteoclastogenesis and bone resorption - Mei Huang; Jingxuan Zhou; Xiaoxiao Li; Ran Liu; Yangzi Jiang; Kaixuan Chen; Yurui Jiao; Xin Yin; Ling Liu; Yuchen Sun; Weishan Wang; Ye Xiao; et al. (Science Bulletin, 2024)

Soot particles formed by n-heptane and n-heptane/oxymethylene ether-3 in an inverse diffusion flame: A comparative analysis of chemical features - Ye Liu; Ran Zhang; Jun Wang; Yajun Wang; Gang Lv; He Yang; Haibo Chen; Tiezhu Li; Bin Hao; Junhua Guo (Fuel, 2024)

Three episodes of Triassic volcanism in the Eastern Kunlun Orogen, NW China: constraints for evolution of the Palaeo-Tethys Ocean - Hao-Ran Li; Jian-Feng Qiao; Feng-Yue Sun; Ye Qian; Yan-Zhang Wang; Shahzad Bakht; Hao-Tian Liu; Yan Gu (International Geology Review, 2024)

Unravelling the safety improving and failure mechanisms of a 56.5 Ah high-energy–density Li-ion cell containing solid-state electrolyte - Wei Zhang; Xiaopeng Qi; Min Liu; Bingxue Liu; Yuansen Hu; Jing Ye; Rennian Wang; Bin Li; Changhong Wang; Qian Huang; Bing Yu; Rong Yang; et al. (Chemical Engineering Journal, 2024)

Petrogenesis of the late Cenozoic potassium-rich volcanism in the NW Tibetan Plateau: Constraints on the mantle evolution through post-orogenic events - Masumeh Sargazi; Chuan-Lin Zhang; Zhi-Hao Song; Hong-Ran Wang; Zahid Hussain; Xian-Tao Ye; Wei Wang; Xiao-Fei Du (Lithos, 2024)

Lateral performance of cold-formed steel framed shear walls using slitted sheathing with stiffeners - Ran Deng; Lu Ye; Yu-Hang Wang; Peng Li; Yu Shi (Engineering Structures, 2024)

Complex floral traits shape pollinator attraction to flowering plants in urban greenspaces - Hui Wang; Nan Ran; Hui-Qian Jiang; Qian-Qian Wang; Min Ye; Peter A. Bowler; Xiao-Fang Jin; Zhong-Ming Ye (Urban Forestry & Urban Greening, 2024)

Sulfonate-rich polymer intercalated LDH artificial SEI film to enable high-stability Li-S batteries - Zimujun Ye; Shengjun Zhai; Ran Liu; Mengzhu Liu; Yang Xu; Changwen Li; Xianbao Wang; Tao Mei (Chemical Engineering Journal, 2024)

Sulfur-decorated Fe/C composite synthesized from MIL-88A(Fe) for peroxymonosulfate activation towards tetracycline degradation: Multiple active sites and non-radical pathway dominated mechanism - Jin Qian; Yichu Zhang; Zhijie Chen; Ran Yu; Yin Ye; Rui Ma; Kailong Li; Lingzhen Wang; Dongqi Wang; Bing-Jie Ni (Journal of Environmental Management, 2023)

Characteristics of sedimentary organic carbon burial in the shallow conduit portion of source-to-sink sedimentary systems in marginal seas - Shuqin Tao; Aijun Wang; James T. Liu; Xiang Ye; Thomas M. Blattmann; Chang Ran; Zitong Liu; Liang Wang; Xijie Yin; Hailong Zhang; Li Li; Xiaoyan Ning; et al. (Geochimica et Cosmochimica Acta, 2023)

Long-term impacts of ecosystem restoration on saturated hydraulic conductivity in the Loess Plateau - Hailong Pan; Qihua Ran; Yanyan Hong; Jin Wang; Xiuxiu Chen; Sheng Ye (Journal of Hydrology, 2023)

C4 expansion of Central Asia in the middle Miocene linked to the strengthening Indian monsoon - Jian Wang; Xinying Zhou; Shiqi Wang; Hai Xu; Hermann Behling; Jie Ye; Yan Zheng; Junchi Liu; Yan Wu; Keliang Zhao; Ran Zhang; Xiaoqiang Li (Global and Planetary Change, 2023)

Oxidative potential of heavy-metal contaminated soil reflects its ecological risk on earthworm - Chunmei Ran; Chunguang Liu; Chu Peng; Xinxin Li; Yu Liu; Ye Li; Wenjun Zhang; Hongming Cai; Lei Wang (Environmental Pollution, 2023)

Late Cretaceous – Cenozoic thermal structure and exhumation of the Eastern Tibetan Plateau margin: A doubly-vergent orogenic wedge - Zhiwu Li; Peter J.J. Kamp; Shugen Liu; Ganqing Xu; Kui Tong; Martin Danišík; Zijian Wang; Jinxi Li; Bin Deng; Bo Ran; Yuehao Ye; Wenhui Wu (Earth-Science Reviews, 2023)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Naturally-Occurring Antibodies Against Bim are Decreased in Alzheimer’s Disease and Attenuate AD-type Pathology in a Mouse Model - Jie-Ming Jian; Dong-Yu Fan; Ding-Yuan Tian; Yuan Cheng; Pu-Yang Sun; Cheng-Rong Tan; Gui-Hua Zeng; Chen-Yang He; Ye-Ran Wang; Jie Zhu; Xiu-Qing Yao; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2022)

Research on Transfer Rate of Heavy Metals and Harmful Elements in Traditional Chinese Medicine Extraction and Refining Processes and Product Health Risk Assessment - Dujia Jin; Lin Li; Wujun Dong; Xiangyang Zhu; Xuejun Xia; Renyun Wang; Jun Ye; Ran Li; Zhihua Liu; Xueqing Xu; Lili Gao; Yuling Liu; et al. (Biological Trace Element Research, 2022)

Peripheral Delivery of Ganglioside GM1 Exacerbates the Pathogenesis of Alzheimer’s Disease in a Mouse Model - Chuang-Chuang Yang; Yuan Cheng; Hai-Mei Yang; Yang Chen; Yan-Jiang Wang; Zhi-Qiang Xu; Ye-Ran Wang (Neuroscience Bulletin, 2022)

Ecological thresholds of phytoplankton community across environmental gradients in the harmful algal blooms-frequently-occurring, subtropical coastal waters, East China Sea - Ran Ye; Chunying Ge; Qiong Wang; Qing Xu; Guofeng Xu; Yongkang Yan; Mingli Qin; Yanhong Cai; Yuejun Fei (Acta Oceanologica Sinica, 2021)

Correction to: FACS‑iChip: a high‑efficiency iChip system for microbial ‘dark matter’ mining - Haoze Liu; Ran Xue; Yiling Wang; Erinne Stirling; Shudi Ye; Jianming Xu; Bin Ma (Marine Life Science & Technology, 2021)

FACS-iChip: a high-efficiency iChip system for microbial ‘dark matter’ mining - Haoze Liu; Ran Xue; Yiling Wang; Erinne Stirling; Shudi Ye; Jianming Xu; Bin Ma (Marine Life Science & Technology, 2021)

CSF Brain-Reactive Autoantibodies are Elevated in Patients with Viral Encephalitis - Zhong-Yuan Yu; Jian-Hong Wang; Wei-Wei Li; Ye-Ran Wang; Noralyn B. Mañucat-Tan; Jun Wang; Ju Wang; Gao-Yu Cui; Jie-Xiang Pan; Shui-Xian Zhang; Zu-Juan Liu; Liang Tan; et al. (Neuroscience Bulletin, 2020)

Naturally Occurring Antibodies to Tau Exists in Human Blood and Are Not Changed in Alzheimer’s Disease - Zhong-Yuan Yu; Wei-Wei Li; Hai-Mei Yang; Noralyn B. Mañucat-Tan; Jun Wang; Ye-Ran Wang; Bin-Lu Sun; Zi-Cheng Hu; Li-Li Zhang; Liang Tan; Juan Deng; Yu-Hui Liu (Neurotoxicity Research, 2020)

Correction to: Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Association of the Polygenic Risk Score with the Incidence Risk of Parkinson’s Disease and Cerebrospinal Fluid α-Synuclein in a Chinese Cohort - Wei-Wei Li; Dong-Yu Fan; Ying-Ying Shen; Fa-Ying Zhou; Yang Chen; Ye-Ran Wang; Heng Yang; Jing Mei; Ling Li; Zhi-Qiang Xu; Yan-Jiang Wang (Neurotoxicity Research, 2019)

Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2019)

Interleukin-26 upregulates interleukin-22 production by human CD4+ T cells in tuberculous pleurisy - Min Zhang; Yi-Ran Niu; Jing-Yuan Liu; Xiao-Shan Wei; Xiao-Rong Wang; Lin-Lin Ye; Wen-Bei Peng; Jian-Chu Zhang; Xiao-Nan Tao; Qiong Zhou (Journal of Molecular Medicine, 2019)

Characterization of polysaccharides purified from Lacquer tree seed cakes and its antioxidant activity - Hongxia Chen; Chengzhang Wang; Hao Zhou; Ran Tao; Jianzhong Ye; Wenjun Li (Natural Product Research, 2018)

Characterization, Cytotoxicity, and Genotoxicity of TiO2 and Folate-Coupled Chitosan Nanoparticles Loading Polyprenol-Based Nanoemulsion - Ran Tao; Chengzhang Wang; Changwei Zhang; WenJun Li; Hao Zhou; Hongxia Chen; Jianzhong Ye (Biological Trace Element Research, 2018)

Graphene oxide-coated stir bar sorptive extraction of trace aflatoxins from soy milk followed by high performance liquid chromatography-laser-induced fluorescence detection - Haiyan Ma; Congcong Ran; Mengjiao Li; Jinglin Gao; Xinyu Wang; Lina Zhang; Jing Bian; Junmei Li; Ye Jiang (Food Additives & Contaminants: Part A, 2018)

The biogeographical distribution of tree species-abundance and its relation to climatic factors in mass islands - Xiaoming Li; Chengzhen Wu; Wu Gu; Ran Ye; Haibo Zhang; Ping Qi; Shengqiang Wang; Siying Zhou; Yongjie Wei; Yanhong Cai (Acta Oceanologica Sinica, 2017)

Characteristics of black shale in the Upper Ordovician Wufeng and lower Silurian Longmaxi formations in the Sichuan Basin and its periphery, China - Y.-H. Ye; S.-G. Liu; B. Ran; J. Luba; S.-Y. Wang; W. Sun; D. Yang; C. Luo (Australian Journal of Earth Sciences, 2017)

Antioxidant capacity and identification of the constituents of ethyl acetate fraction from Rhus verniciflua Stokes by HPLC-MS - Hongxia Chen; Chengzhang Wang; Hao Zhou; Ran Tao; Jianzhong Ye; Wenjun Li (Natural Product Research, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Associations Between Hepatic Functions and Plasma Amyloid-Beta Levels—Implications for the Capacity of Liver in Peripheral Amyloid-Beta Clearance - Ye-Ran Wang; Qing-Hua Wang; Tao Zhang; Yu-Hui Liu; Xiu-Qing Yao; Fan Zeng; Jing Li; Fa-Yin Zhou; Lin Wang; Jia-Chuan Yan; Hua-Dong Zhou; Yan-Jiang Wang (Molecular Neurobiology, 2017)

Identification of coastal water quality by multivariate statistical techniques in two typical bays of northern Zhejiang Province, East China Sea - Ran Ye; Lian Liu; Qiong Wang; Xiansen Ye; Wei Cao; Qinyan He; Yanhong Cai (Acta Oceanologica Sinica, 2017)

Biosorption and degradation of decabromodiphenyl ether by Brevibacillus brevis and the influence of decabromodiphenyl ether on cellular metabolic responses - Linlin Wang; Litao Tang; Ran Wang; Xiaoya Wang; Jinshao Ye; Yan Long (Environmental Science and Pollution Research, 2016)

Sex Dimorphism Profile of Alzheimer’s Disease-Type Pathologies in an APP/PS1 Mouse Model - Shu-Sheng Jiao; Xian-Le Bu; Yu-Hui Liu; Chi Zhu; Qing-Hua Wang; Lin-Lin Shen; Cheng-Hui Liu; Ye-Ran Wang; Xiu-Qing Yao; Yan-Jiang Wang (Neurotoxicity Research, 2016)

Serum Amyloid-Beta Levels are Increased in Patients with Chronic Obstructive Pulmonary Disease - Xian-Le Bu; Guo-Qiang Cao; Lin-Lin Shen; Yang Xiang; Shu-Sheng Jiao; Yu-Hui Liu; Chi Zhu; Fan Zeng; Qing-Hua Wang; Ye-Ran Wang; Yong He; Hua-Dong Zhou; et al. (Neurotoxicity Research, 2015)

Association Between Serum Amyloid-Beta and Renal Functions: Implications for Roles of Kidney in Amyloid-Beta Clearance - Yu-Hui Liu; Yang Xiang; Ye-Ran Wang; Shu-Sheng Jiao; Qing-Hua Wang; Xian-Le Bu; Chi Zhu; Xiu-Qing Yao; Brian Giunta; Jun Tan; Hua-Dong Zhou; Yan-Jiang Wang (Molecular Neurobiology, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Genetic Association Between APP, ADAM10 Gene Polymorphism, and Sporadic Alzheimer’s Disease in the Chinese Population - Fan Zeng; Cheng Shen; Yu-Hui Liu; Jing Li; Jie Zhu; Ye-Ran Wang; Jia-Chuan Yan; Chang-Yue Gao; Hua-Dong Zhou; Juan Deng; Yan-Jiang Wang (Neurotoxicity Research, 2015)

Serum Aβ is Predictive for Short-Term Neurological Deficits After Acute Ischemic Stroke - Yu-Hui Liu; Hong-Yuan Cao; Ye-Ran Wang; Shu-Sheng Jiao; Xian-Le Bu; Fan Zeng; Qing-Hua Wang; Jing Li; Juan Deng; Hua-Dong Zhou; Yan-Jiang Wang (Neurotoxicity Research, 2015)

Clearance of Amyloid-Beta in Alzheimer’s Disease: Shifting the Action Site from Center to Periphery - Yu-Hui Liu; Ye-Ran Wang; Yang Xiang; Hua-Dong Zhou; Brian Giunta; Noralyn B. Mañucat-Tan; Jun Tan; Xin-Fu Zhou; Yan-Jiang Wang (Molecular Neurobiology, 2015)

A Combinatorial Yeast Overlay Method for the Isolation of Antibacterial Oligopeptides - Ran He; Liang Cui; Yan Cao; Zhixue Wang; Kai Wang; Min Fu; Shaoyun Song; Chuanfu Dong; Xiaoxuan Wu; Ye Gao; Xiaoxiao Zhang; Fan Feng; et al. (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Identification of a Novel Mutation in the Presenilin 1 Gene in a Chinese Alzheimer’s Disease Family - Bo Deng; Yan Lian; Xin Wang; Fan Zeng; Bin Jiao; Ye-Ran Wang; Chun-Rong Liang; Yu-Hui Liu; Xian-Le Bu; Xiu-Qing Yao; Chi Zhu; Lu Shen; et al. (Neurotoxicity Research, 2014)

Nitratireductor shengliensis sp. nov., Isolated from an Oil-Polluted Saline Soil - Xin-Chi Pan; Shuang Geng; Ran Mei; Ya-Nan Wang; Hua Cai; Xue-Ying Liu; Yue-Qin Tang; Yong Nie; Si-Yuan Ye; Xiao-Lei Wu (Current Microbiology, 2014)

The Pseudomonas aeruginosa Mannose Sensitive Hamemagglutination Strain (PA-MSHA) Induces a Th1-Polarizing Phenotype by Promoting Human Dendritic Cells Maturation - Yunyan Zhang; Hongtao Wang; Youqiang Li; Ke Chen; Jinmei Ye; Xin Liao; Yiyang Chen; Wei Ran (Indian Journal of Microbiology, 2014)

Lipopolysaccharides Reduce Adipogenesis in 3T3-L1 Adipocytes Through Activation of NF-κB Pathway and Downregulation of AMPK Expression - Lifeng Wang; Linlin Li; Xinjian Ran; Mei Long; Minfang Zhang; Yicun Tao; Xin Luo; Ye Wang; Yi Jiao; Xinmin Mao; Jun Ren (Cardiovascular Toxicology, 2013)

A “GC-rich” method for mammalian gene expression: A dominant role of non-coding DNA GC content in regulation of mammalian gene expression - Qian Jia; HongTao Wu; XingJun Zhou; Jian Gao; Wei Zhao; JouDi Aziz; JingShuang Wei; Lihua Hou; Shuyin Wu; Ying Zhang; XiangFeng Dong; YanMin Huang; et al. (Science China Life Sciences, 2010)

The Prevalence of Type 2 Diabetes and Hypertension in Uygur and Kazak Populations - Yicun Tao; Xinmin Mao; Zijing Xie; Xinjian Ran; Xiaoyan Liu; Ye Wang; Xin Luo; Mengying Hu; Wenning Gen; Minfang Zhang; Tao Wang; Jun Ren; et al. (Cardiovascular Toxicology, 2008)

Analysis of Prevalence and Risk Factors of Hypertension Among Uygur Adults in Tushala and Hetian Xinjiang Uygur Autonomous Region - Lin-Lin Li; Xiao-Yan Liu; Jian-Xin Ran; Ye Wang; Xin Luo; Tao Wang; Jun Ren; Mayinuer Aisha; Rebiya Abudureheman; Adalaiti Xiawudong; Xiao-Chun Zhang; Xin-Min Mao (Cardiovascular Toxicology, 2008)

A two-dimensional electrophoresis reference map of human ovary - Lei Wang; Ye-Fei Zhu; Xue-Jiang Guo; Ran Huo; Xiang Ma; Min Lin; Zuo-Min Zhou; Jia-Hao Sha (Journal of Molecular Medicine, 2005)